THE PROBLEM OF FORMATION OF LOCAL HISTORY PRINCIPLES AND LOCAL STUDIES IN THE WORKS OF SCIENTISTS (Pedagogy of Higher and Secondary Education, 2022)
The article is devoted to the retrospective analysis of the development o f the local lore principle and study of local lore in the pedagogical literature.